An Investigation of the Relationship between Manufacturing Output and Economic Growth : Evidence from Nigerias Data Set - Fatai, Ogunlana Olarewaju (International Journal of Business, Economics and Management, 2018)
This paper examined the relationship between manufacturing output and economic growth using Nigeria’s data set for empirical testing. The study adopts cointegration technique, error correction mechanism and granger causality test to investigate the long run, short run dynamics and causal relationship between manufacturing output and economic growth. The key variables employed in the estimation are technology, domestic investment, lending rate to private investors, foreign direct investment inflows, capacity utilization rate, foreign exchange rate and price movement. The cointegration tests suggests that long run relationship exists among the variables employed in the estimation. Findings from the long run and short run estimation shows that gross fixed capital formation, capacity utilization rate, foreign direct investment inflows, price movement, technology and lending rate to private investors are credible determinants of manufacturing output in Nigeria. The causality test suggests a unidirectional relationship between economic growth and observed manufacturing output. Policy direction is instructive towards achieving sustainable industrial growth and development.